Effect of Social Capital on Tertiary Preventive Behavior among Older Adults with Type 2 Diabetes Mellitus: A Structural Equation Modeling Approach - Anna Nugrahani; Bhisma Murti; Setyo Sri Rahardjo; Argyo Demartoto; Revi Gama Hatta Novika (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Diabetes Mellitus (DM), known as the “silent killer,” continues to show an increasing number of cases. It has emerged as one of the most serious and common chronic diseases, leading to life-threatening complications, disability, and reduced life expectancy. The persistently high prevalence of diabetes in Karanganyar Regency, along with the interaction among multiple determinants, underlies the objective of this study, which is to analyze the influence of structural, cognitive, and relational social capital models on tertiary preventive behavior among elderly individuals with Type 2 Diabetes Mellitus. Subjects and Method: This study employed a cross-sectional design. It was conducted in Karanganyar Regency (Jatipuro, Jatiyoso, and Karanganyar sub-districts), Central Java, from January to March 2025. A total of 210 elderly participants were selected using certified random sampling. Data were collected using a structured questionnaire. The analyses included univariate, bivariate, and multivariate analyses using a structural equation model (SEM). The dependent variable was tertiary preventive behavior among elderly individuals with Type 2 Diabetes Mellitus. The independent variables were social capital, comprising structural social capital, cognitive social capital, and relational social capital. Results: Structural social capital had a positive and statistically significant effect on tertiary preventive behavior (b= 0.32; 95% CI= 0.13 to 0.52; p= 0.001). Relational social capital also showed a positive and significant effect on tertiary preventive behavior (b= 0.37; 95% CI= 0.15 to 0.59; p= 0.001). Age demonstrated a negative and statistically significant effect on tertiary preventive behavior (b= -0.09; 95% CI= -0.16 to -0.03; p= 0.003). Conclusion: The findings of this study indicate that elderly individuals with Type 2 Diabetes Mellitus who have higher levels of social capital—comprising structural, cognitive, and relational dimensions—are more likely to engage in tertiary preventive behaviors.